The role of location in the functioning of a local currency: La Gonette case study - Lakócai, Csaba (European Spatial Research and Policy, 2021)
The beginning of the 21st century was a proliferation of complementary currencies worldwide. Among them, a number of newly created local currencies were notable. France proved to be especially fertile in this regard from the early 2010s. La Gonette, operating in the metropolitan area of Lyon, is one of the biggest French local complementary currencies in terms of its users, providers (business partners), and money supply. For every scheme, the most important issue, which is also a challenge, is to provide enough spending options to be attractive for users, while also retaining their particular sociocultural identity. Besides a variety of spending options, their location features are also important in regards to future development, so decision-makers of a scheme can diversify the business expansion strategy accordingly in order to better achieve the desired socio-economic goals. Using la Gonette as a case study, the research objective of this paper is to uncover the implications of the providers’ location on the functioning of the scheme. To address this objective, I applied statistical tests for correspondence on the providers’ categorical and locational breakdowns. The results have shown heterogeneity in the spatial distribution of the types of providers in accordance with broader location characteristics, a fact which supports the need for territorial diversification of future development concepts.